"Creating Wealth" through Debt: The West's Finance-Capitalist Road. (1st July 2019) - Hudson, Michael
Abstract : Volumes II and III of Marx's Capital describe how debt grows exponentially, burdening the economy with carrying charges. What policies are best suited for China to avoid this neo- rentier disease while raising living standards in a fair and efficient low-cost economy? The most pressing policy challenge is to keep down the cost of housing. Rising housing prices mean larger and larger debts extracting interest out of the economy. The strongest way to prevent this is to tax away the rise in land prices, collecting the rental value for the government instead of letting it be pledged to the banks as mortgage interest. The same logic applies to public collection of natural resource and monopoly rents. The US and European business schools are part of the problem, not part of the solution. They teach the tactics of asset stripping and how to replace industrial engineering with financial engineering, as if financialization creates wealth faster than the debt burden. Having rapidly pulled ahead over the past three decades, China must remain free of rentier ideology that imagines wealth to be created by debt-leveraged inflation of real-estate and financial asset prices.